Complex 3D‐Printed Microchannels within Cell‐Degradable Hydrogels. (7th June 2018) - Song, Kwang Hoon; Highley, Christopher B.; Rouff, Andrew; Burdick, Jason A.
Abstract: 3D‐printing is emerging as a technology to introduce microchannels into hydrogels, for the perfusion of engineered constructs. Although numerous techniques have been developed, new techniques are still needed to obtain the complex geometries of blood vessels and with materials that permit desired cellular responses. Here, a printing process where a shear‐thinning and self‐healing hydrogel "ink" is injected directly into a "support" hydrogel with similar properties is reported. The support hydrogel is further engineered to undergo stabilization through a thiol‐ene reaction, permitting (i) the washing of the ink to produce microchannels and (ii) tunable properties depending on the crosslinker design. When adhesive peptides are included in the support hydrogel, endothelial cells form confluent monolayers within the channels, across a range of printed configurations (e.g., straight, stenosis, spiral). When protease‐degradable crosslinkers are used for the support hydrogel and gradients of angiogenic factors are introduced, endothelial cells sprout into the support hydrogel in the direction of the gradient. This printing approach is used to investigate the influence of channel curvature on angiogenic sprouting and increased sprouting is observed at curved locations. Ultimately, this technique can be used for a range of biomedical applications, from engineering vascularized tissue constructs to modeling in vitro cultures. Abstract : Complex microchannels of various shapes are 3D printed within a hydrogel that supports cell adhesion and invasion through cell‐mediated hydrogel degradation. Seeded endothelial cells respond to gradients of angiogenic factors to form sprouts based on hydrogel degradability and protease activity. Sprouting is observed to depend on microchannel curvature.